Currículo avaliado do estado de São Paulo e SARESP de Geografia - Lemos, Marcela Araujo de Mello (2018)
The study aims to analyze geography curriculum of São Paulo state, as product of the 2008 São Paulo Faz Escola program, from SARESP evaluation applied to elementary school between 2009 and 2013. To achieve this goal, the following documents were consult as a primary source: Curricular Proposal of São Paulo State (2010), Array of Reference for Evaluation – SARESP (2009), SARESP Educational Reports (2009, 2010 and 2013) and Geography Notebooks for Teachers (2014). Finally, the Students Newspaper (2008) as secondary source. This research justifies the relevance when considering that the São Paulo Faz Escola program, created by the government of São Paulo state in 2008, aimed at improving the quality of education in accordance with the proposals linked to the interests of the major international institutions, like the World Bank. Therefore, the hypothesis is that SARESP is an assessment designed to shape the curriculum. This hypothesis confirmed when noticed the poor quality of the items produced for evaluation, containing conceptual errors and incompatibility between the skill and the theme of the question. In addition, the Array of Reference for Evaluation containing the guidelines for the SARESP was a document prepared and published before the Curricular Proposal of São Paulo, configuring this curriculum as assessed conformed to the reports of international institutions